Electricity carbon accounting framework for China’s regional power grids: a case study of the Southern Power Grid - Huang, Yanlu; Hu, Xudong; Zhang, Fan; Pan, Shixian; Tan, Junfeng (Frontiers in Energy Research, 2024)
Over 40% of China's emissions come from the power industry, and regional power grids are crucial to the country's ability to transmit and distribute electricity. However, there is a lack of a complete framework on electricity-related carbon emissions accounting for regional power grids across different stages of electricity production and distribution. Here, we propose a framework for accounting for carbon emissions in electricity for regional power networks.Using the Southern Power Grid as a case study, we estimate carbon intensity across various stages of electricity generation, supply, and consumption. We incorporate the temporal and regional variations to analyze carbon emissions across five provinces (Guangdong, Guangxi, Yunnan, Guizhou, and Hainan), identifying key trends and factors that influence carbon intensity. Our framework integrates data from multiple sources, including real-world emissions and renewable energy inputs, while validating results through method comparisons and realtime policy alignment. The results reveal significant disparities in carbon intensity reduction across provinces, with Yunnan achieving the most notable reduction and Guangdong showing the highest emissions on the consumption side. Our framework is versatile, reliable, and applicable to other regional grids in China, offering a critical tool for projecting future electricity-related carbon emissions and supporting the nation's carbon neutrality goals.